DESIGN OF MARKETING PLAN FOR DENTAL HOSPITALS IN THE DIGITAL ERA - Yusuf Arifin; Jane Firsty Melia; Fushen Fushen (Indonesian Journal of Health Administration, 2022)
Background: The development of the digital world has snowballed since the 2000s and has accelerated since the 2010s. Social media is a part of everyday life, and the COVID-19 pandemic has been a significant catalyst for digital life. Despite this, the healthcare industry is lagging compared to other industries in terms of digital marketing. Aims: The output of this research is a design of a digital marketing plan for a dental hospital based on a robust theoretical foundation and ongoing practical research in dental hospitals. Methods: This study utilized a qualitative approach and descriptive method to describe the existing condition related to the challenges and the use of digital marketing in dental hospitals. The focus of this study was the development of a digital marketing plan for a dental hospital. Results: The study obtained several data related to digital marketing activities that have been carried out, challenges in digital marketing, and the preparation of digital marketing development plans at dental hospitals. Conclusion: The proposed model includes situation analysis, goal analysis, strategy planning, action, and control based on the existing marketing plan. A novelty in this model emphasizes technology components including technoware, hardware, software, infoware, humanware, and organiware.